Internalization of Religious Character Values through Reading and Writing Literacy of the Qur'an in Madrasah Ibtidaiyah Students - Syahrul; Ahmad Taufik (Journal of Educational Management Research, 2026)
The goal of strengthening religious character in Madrasah Ibtidaiyah education is often overshadowed by a focus on cognitive and technical skills. Qur'anic literacy, encompassing reading and writing, holds significant potential for internalizing religious values, but studies on this process are limited. This qualitative case study analyzes how Qur'anic literacy helps internalize religious character values in Madrasah Ibtidaiyah students, focusing on grades IV, V, and VI. Data was collected from teachers, students, and madrasah heads through interviews, observations, and documentation. The findings show that Qur'anic literacy goes beyond technical skills and serves as a medium for instilling values like discipline, responsibility, dedication to learning, and respect for the Qur'an. The internalization process is facilitated through teacher role models, habit formation, and value reinforcement integrated into literacy activities. This research suggests practical ways to enhance religious character education in Madrasah Ibtidaiyah by optimizing Qur'anic literacy.